Online Game Addiction Behavior in Teenagers - Moch Farhan Kamil; Nur Maghfirah Aestetika (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to understand and find out about addictive behavior in playing online games Higgs Domino Island among teenagers. ” which has an addictive effect on the players. This research method uses qualitative methods, the informant determination technique used in this study is the purposive sampling technique, data collection obtained from interviews, observations and documentation. The results of this study indicate that all informants have addictive behavior towards the Higgs Domino Island internet game with different levels. This level consists of salience, tolerance, mood swings, relapse, withdrawal, conflict, and problems.